2016
DOI: 10.1007/s13205-016-0406-x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and characterization of a thermostable, alkali-tolerant chitinase from Bacillus pumilus JUBCH08 displaying antagonism against phytopathogenic Fusarium oxysporum

Abstract: The present investigation highlights the process parameters influencing the submerged fermentation of chitinase by Bacillus pumilus JUBCH08, purification and characterization of the enzyme and determination of antagonistic activity of the bacterium against Fusarium oxysporum. Medium supplemented with 0.5 % chitin and peptone, at initial pH 8.0, when incubated at 35 °C for 72 h favored highest chitinase production. The enzyme was purified 25.1-fold to homogeneity. The chitinase was found to be thermostable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…3). Similar results have been reported where maximum chitinase secretion was found after 48 hours of incubation [23,24]. The isolate GS02 showed production of chitinase within first 24 hours and reached to its maximum level after 48 hours of incubation.…”
Section: Optimization Of Culture Conditions Of Isolated Strainsupporting
confidence: 88%
See 1 more Smart Citation
“…3). Similar results have been reported where maximum chitinase secretion was found after 48 hours of incubation [23,24]. The isolate GS02 showed production of chitinase within first 24 hours and reached to its maximum level after 48 hours of incubation.…”
Section: Optimization Of Culture Conditions Of Isolated Strainsupporting
confidence: 88%
“…6). Bhattacharya et al [23] also showed maximum production of chitinase by Bacillus sp. between the temperature 35 to 37°C.…”
Section: Optimization Of Culture Conditions Of Isolated Strainmentioning
confidence: 94%
“…This may be caused by the mechanical forces that can lead to vacuolation of older hyphal compartments, which may lead to weakened hyphae and/or enhancing hyphal fragmentation (Paul et al, 1994). A similar finding was obtained by Bhattacharya et al (2016) who recorded that maximum production of chitinase from Bacillus pumilus was at 120 rpm.…”
Section: Discussionsupporting
confidence: 68%
“…In agriculture, the inhibitory properties of chitinases are being harnessed for the biological control of pests and fungal diseases of plants. The control of fungal phytopathogens such as Trichoderma reesei [ 98 ], Colletotrichum gleosporoides [ 99 ], Phoma medicaginis [ 100 ], Rhizoctonia solani [ 101 ], Fusarium oxysporum [ 102 ], and Fusarium graminarium [ 103 ] has been reported.…”
Section: Implications Of Variations Among Chitinases For Optimizationmentioning
confidence: 99%